Coping strategies of a rape victim as reflected in Chanel Miller’s Know My Name memoir - Maghfira, Raudya; Lailiyah, Malikhatul (D3 English Program Universitas Merdeka Malang, 2021)
Memoir is a literary work genre that belongs to the subgenre of autobiography. Most of the memoir showcases the writer’s particular moment of life, rather than the reels of their whole life. Chanel Miller, for example, showcases her experience during the aftermath of rape in her memoir, Know My Name. Various definition of rape has one thing in common, which rape is something that happens despite the lack of consensus and that creates stress after it happens. Stressful encounters require a coping strategy to conquer them. This study tries to analyze coping strategies on Know My Name memoir because it is due time for us to recognize how rape has influenced the victim’s life to provide better care both physical and psychological wise for rape victims and, even better, to formulate better law to protect the victim. Using descriptive study, the important features were found as Channel Miller’s emotional reactions to choose a way out of the problem.